Pelaksanaan Dental Health Education (DHE) dalam meningkatkan status kebersihan gigi dan mulut pada murid SDN 33 Kota Banda Aceh - Reca Reca; Ainun Mardhiah; Cut Aja Nuraskin (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Dental and oral health is one part that can not be separated from overall body health. Dental and oral care as a whole begins with dental and oral hygiene for each individual. Teaching methods of brushing teeth for children need to be given examples of a good model and with the simplest technique possible.Objectives: The research aims to increase the knowledge of SDN 33 Banda Aceh City students in maintaining dental and oral health and improve the dental and oral hygiene status of SDN 33 Banda Aceh City students.Method:  The research using a quantitative method with a descriptive approach, with the target of Class V students of SDN 33 Banda Aceh City Banda Aceh City totaling 30 children. Data analysis uses univariate analysis. The interventions provided were in the form of Dental Health Education (DHE).Results: The results of these community service activities show there is an increase in students' knowledge in the maintenance of dental and oral hygiene in SDN 33 Banda Aceh City students, with an increase before the intervention (pre-test) is in the sufficient category (56.7%) and after the intervention (post test) in the good category (96.7%). There was an increase in the status of dental and oral hygiene of students, with an increase before the intervention (pre-test) was in the bad category (100%) and after the intervention (post test) was in the good category (100%).Conclusion: It is recommended that schools provide regular counseling to students about the importance of maintaining oral health and holding joint toothbrushes to improve oral and dental hygiene.